Doctors' Perceptions of Rare Bone Disorders and X-Linked Hypophosphatemia: A Survey from Africa and the Middle East - Beshyah, Waleed S.; Alsaffar, Hussain; Beshyah, Salem A. (Journal of Diabetes and Endocrine Practice, 2022)
Objectives To assess the perceptions of genetic and metabolic bone disorders with a focus on X-linked hypophosphatemia (XLH) in the Middle East and Africa.Materials and Methods An online survey of a convenience sample of physicians from relevant disciplines. The questions covered respondents' profiles, awareness of rare bone diseases, and XLH's burden, symptoms, and management.Results A total of 139 respondents were included in the analysis. Responses came from the Arabian Gulf (41.7%), Middle East (20.1%), North Africa (17.3%), and Sub-Saharan Africa (20.9%). The largest single specialty was endocrinology (41%). When asked, 16 (11.5%) could not know about any metabolic/genetic bone diseases, and 123 respondents (88.5%) stated that they could think/were aware of some metabolic/genetic bone diseases, 111 enumerated various genetic and metabolic disorders. When they were presented with a typical case scenario of XLH, 18.0% of the respondents admitted ignorance of any possibility. However, 82.0% indicated having some idea of the condition. Of the latter group, 109 provided suggestions for possible diagnosis; the top single diagnosis was XLH. A smaller proportion of adult physicians had patients with symptoms attributed to XLH. Around three-quarters of respondents were aware of conventional therapy for XLH with vitamin D and phosphate supplementation. However, 89.8% of respondents welcomed specific biological therapy.Conclusions Physicians are reasonably aware of XLH but have variable knowledge. They are unsatisfied with its conventional treatment. More in-depth knowledge of recognizing and modern management of bone metabolic and genetic conditions should be enhanced, particularly among adult physicians.
Keywords: hypophosphatemia; rickets; X-linked hypophosphatemia (XLH); genetic bone diseases; metabolic bone diseases; rare bone diseases; Burosumab